10y-2=7+3G

Simple and best practice solution for 10y-2=7+3G equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10y-2=7+3G equation:


Simplifying
10y + -2 = 7 + 3G

Reorder the terms:
-2 + 10y = 7 + 3G

Solving
-2 + 10y = 7 + 3G

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 10y = 7 + 2 + 3G

Combine like terms: -2 + 2 = 0
0 + 10y = 7 + 2 + 3G
10y = 7 + 2 + 3G

Combine like terms: 7 + 2 = 9
10y = 9 + 3G

Divide each side by '10'.
y = 0.9 + 0.3G

Simplifying
y = 0.9 + 0.3G

See similar equations:

| 3b^2-b-7=4b(2b+3)-1 | | x/4=9/(2*x) | | 12n+3=-12n^2 | | 9x-14=40 | | 6h=4h^3+5h^2 | | 3m(2m+5)-8=2m(3m+5)+2 | | 3.5(x+2.2y)+2(2.2x+1.7y)= | | (-9y-2z)(-8)= | | 1/16w^2+1/8w=1/2 | | 3d-4=d(d+8) | | 44x-4x=5x+18 | | -7-5x=5x+21 | | 10a+8b+4c-8d=7 | | 1-x=0.4 | | x^10=0.6 | | 6/7t=-48 | | 1-(x^10)=0.4 | | 5x-3=13-67 | | 2.8=14/x | | 2(r+5)=10-4r^2 | | 3t^3+5t=-8t^2 | | 2x^2y-5xy^2=0 | | (2x-3)(5x^2-2x+1)= | | z^2-20=22-z | | (-7x^3-2x-4)-(8x^2+4x-7)= | | 2x^2-6x+1=o | | 2p(p+4)=p^2+5p+10 | | 6y-8=40 | | 1/2+4/7p | | x+1.05x=20 | | -3(x+4)=24 | | 13c=2c^2+6 |

Equations solver categories